Sodium ion positive electrode material and preparation method and composition thereof

By doping Ca2+ on sodium and transition metal doping Ti, Mg and other elements, the molar ratio of sodium and calcium is controlled to form a more stable crystal structure, which solves the high capacity of O3 layered oxide sodium ion positive electrode material at high voltage The problem of difficulty in coexisting with long cycle stability has achieved the improvement of specific capacity and cycle stability and the improvement of discharge median voltage.

CN119153676AActive Publication Date: 2024-12-17HUNAN MEITE XINCAILIAO SCI & TECH CO LTD

Patent Information

Application Number
CN202411481374.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2024-12-17
Estimated Expiration
2044-10-23

AI Technical Summary

Technical Problem

The existing O3 layered sodium oxide positive electrode material has the problem of difficult coexistence of high capacity and long cycle stability under high operating voltages, and the existing doping and oxide coating methods are not effective.

Method used

Sodium doping Ca2+ and transition metal doping elements such as Ti, Mg are used to control the molar ratio of sodium and calcium to form a more stable crystal structure, and improve the specific capacity and cyclic stability of O3-type sodium ion battery materials.

Benefits of technology

At an operating potential above 4.15V, the median discharge voltage and cyclic stability are effectively improved, taking into account the specific capacity and cyclic stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153676A_ABST
    Figure CN119153676A_ABST
Patent Text Reader

Abstract

The invention provides a sodium ion positive electrode material and a preparation method and a composition thereof, the chemical formula of the sodium ion positive electrode material is NaxCayNiaFebMncTidTMeO2, TM is at least one of Mg, Sr, Zr, Y, Al, La, Zn and Nb metal elements and inevitably contains Mg, 0.5 < = x < = 1.1, 0.01 < = y < = 0.1, 0.1 < = a < = 0.5, 0.05 < = b < = 0.3, 0.1 < = c < = 0.4, 0.01 < = d < = 0.3 and 0.01 < = e < = 0.1, and the sodium ion positive electrode material is an O3 type sodium ion positive electrode material. According to the sodium ion positive electrode material, Ca < 2 + > is doped in the sodium site, the molar ratio of sodium to calcium is controlled at the same time, and Ti and Mg are used as necessary doping elements of transition metal sites, so that the O3 type sodium ion positive electrode material can form a more stable crystal structure. After the working potential is increased to be higher than 4.15 V, the O3-type sodium-ion battery material has both specific capacity and cycling stability, and the discharge median voltage is effectively increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery materials, and in particular to a sodium ion positive electrode material and a preparation method and a composition thereof. Background Art

[0002] The chemical formula of O3 layered oxide is NaxTMO 2 , (x≥0.8, TM is at least one of the transition metal elements Ni, Fe, Mn, etc.). O3 layered oxides are NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O 2 For example, it undergoes a continuous O3-P3-O3' phase transition at a high cut-off voltage (>4.1V). This multiphase transition will induce significant lattice distortion and volume strain, and produce cracks and nano-voids inside the crystal, which will lead to lattice oxygen reaction, metal layer slip, interlayer cation mixing, and destroy the structural stability. The above problems lead to Na x TMO 2 There is a technical problem that positive electrode materials have high capacity and long cycle stability and cannot coexist under high working voltage. The existing technology has not yet achieved satisfactory results in solving the above problems by means of transition metal ion doping and oxide coating. Summary of the invention

[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a sodium ion positive electrode material and a preparation method and composition thereof.

[0004] To achieve the above object, the technical solution adopted by the present invention is: a sodium ion positive electrode material, the chemical formula of the sodium ion positive electrode material is Na x Ca y Ni a Fe b Mn c Ti d TM e O 2 , wherein TM is at least one of Mg, Sr, Zr, Y, Al, La, Zn, and Nb metal elements and must contain Mg, 0.5≤x≤1.1, 0.01≤y≤0.1, 0.1≤a≤0.5, 0.05≤b≤0.3, 0.1≤c≤0.4, 0.01≤d≤0.3, 0.01≤e≤0.1, and the sodium ion positive electrode material is an O3 type sodium ion positive electrode material.

[0005] In the process of studying the sodium doping of O3 type sodium ion positive electrode materials, the inventors found that the sodium doping of O3 type sodium ion battery materials alone is not sufficient to improve the high capacity and long cycle stability of O3 type sodium ion positive electrode materials at high voltage. The inventors considered that the sodium doping of O3 type sodium ion positive electrode materials and the doping of transition metals at the position are beneficial to improving the high capacity and long cycle stability of O3 type sodium ion battery materials at high voltage, and found that the sodium doping of O3 type sodium ion positive electrode materials with Ca 2+ The transition metal sites are doped with Ti, Mg and other elements, and Ti and Mg are used as necessary doping elements for the transition metal sites. When the doping element amounts are the same, the sodium site is doped with Ca 2+ By controlling the molar ratio of sodium and calcium at the same time and using Ti and Mg as necessary doping elements at the transition metal position, the O3 type sodium ion positive electrode material can form a more stable crystal structure. After the working potential is increased to above 4.15V, the above O3 type sodium ion battery material takes into account both specific capacity and cycle stability and effectively increases the discharge median voltage.

[0006] Preferably, TM is at least two of the metal elements Mg, Sr, La, Al, Y, and Nb and necessarily contains Mg.

[0007] Doping Ca at the sodium site of O3-type sodium ion cathode materials 2+ The transition metal sites are doped with Ti, Mg and other elements, and Ti and Mg are used as necessary doping elements for the transition metal sites. When the doping element amounts are the same, the sodium site is doped with Ca 2+ And at the same time, the molar ratio of sodium and calcium is controlled, and Ti and Mg are used as necessary doping elements at the transition metal position, and Sr, Zr, Y or Al is doped in the transition metal layer, so that the O3 type sodium ion battery material can take into account both specific capacity and cycle stability, with better specific capacity and cycle stability while increasing the discharge median voltage.

[0008] Preferably, TM is two or three of Mg, Sr, and Y and necessarily contains Mg.

[0009] The above-mentioned O3 type sodium ion positive electrode material has better specific capacity and cycle stability while improving the discharge median voltage.

[0010] Preferably, 0.8≤x≤1.1, 0.01≤y≤0.05, 0.25≤a≤0.50, 0.1≤b≤0.25, 0.2≤c≤0.35, 0.1≤d≤0.3, and 0.02≤e≤0.05.

[0011] Preferably, 0.95≤x≤1.05, 0.02≤y≤0.03.

[0012] The above-mentioned O3-type sodium ion positive electrode material controls the molar ratio of sodium and calcium, which is beneficial to improving the specific capacity, cycle performance and discharge median voltage of the battery material.

[0013] Preferably, the method for preparing the sodium ion positive electrode material comprises the following steps:

[0014] Ni a Fe b Mn c Ti d (OH) 2 The precursor is fully mixed with the sodium source, the calcium source and the TM source in a stoichiometric ratio, calcined at 700-900° C. for 1.5-2.5 hours, then heated to 900-1000° C. for 10-14 hours, and then cooled naturally to obtain the sodium ion positive electrode material.

[0015] Preferably, the method comprises the following steps:

[0016] Ni a Fe b Mn c Ti d (OH) 2 The precursor is fully mixed with the sodium source, the calcium source and the TM source in a stoichiometric ratio, calcined at 700-900° C. for 1.5-2.5 hours, then heated to 900-1000° C. for 10-14 hours, and then cooled naturally to obtain the sodium ion positive electrode material;

[0017] The sodium source is sodium carbonate, the calcium source is calcium carbonate or calcium oxide, and the TM source is the oxide or hydroxide of the corresponding element.

[0018] The present invention also provides a material composition for a sodium ion battery positive electrode, comprising 80 to 100 parts by weight of any of the sodium ion positive electrode materials described above, 4 to 6 parts by weight of conductive carbon black, and 4 to 6 parts by weight of polyvinylidene fluoride.

[0019] The combination of the above-mentioned material composition for the sodium ion battery positive electrode can better exert the specific capacity and cycle performance of the sodium ion positive electrode material and improve the discharge median voltage.

[0020] The present invention also provides a battery positive electrode, comprising 80 to 100 parts by weight of any of the above-mentioned sodium ion positive electrode materials, 4 to 6 parts by weight of conductive carbon black, and 4 to 6 parts by weight of polyvinylidene fluoride.

[0021] The beneficial effects of the present invention are as follows: the present invention provides a sodium ion positive electrode material and a preparation method and composition thereof, wherein the sodium ion positive electrode material of the present invention is doped with Ca 2+By controlling the molar ratio of sodium and calcium at the same time and using Ti and Mg as necessary doping elements at the transition metal position, the O3 type sodium ion positive electrode material can form a more stable crystal structure. After the working potential is increased to above 4.15V, the above O3 type sodium ion battery material takes into account both specific capacity and cycle stability and effectively increases the discharge median voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is a SEM image of a sodium ion positive electrode material according to an embodiment of the present invention.

[0023] Figure 2 This is an XRD diagram of a sodium ion positive electrode material according to an embodiment of the present invention.

[0024] Figure 3 This is the 0.1C first charge and discharge curve of the sodium ion positive electrode material of Example 1 of the present invention.

[0025] Figure 4 This is a cycle performance diagram of the sodium ion positive electrode material of Example 1 of the present invention.

[0026] Figure 5 This is a SEM image of a sodium ion positive electrode material according to an embodiment of the present invention.

[0027] Figure 6 This is an XRD diagram of a sodium ion positive electrode material according to an embodiment of the present invention.

[0028] Figure 7 This is the 0.1C first charge and discharge curve of the sodium ion positive electrode material of Example 3 of the present invention.

[0029] Figure 8 This is a cycle performance diagram of the sodium ion positive electrode material of Example 3 of the present invention.

[0030] Fig. 9 This is a SEM image of a sodium ion positive electrode material of the comparative example of the present invention.

[0031] Fig.10 This is an XRD diagram of a sodium ion positive electrode material of the comparative example of the present invention.

[0032] Fig.11 This is the 0.1C first charge and discharge curve of the sodium ion positive electrode material of Comparative Example 1 of the present invention.

[0033] Fig.12 This is a cycle performance diagram of the sodium ion positive electrode material of Comparative Example 1 of the present invention.

[0034] Fig.13 This is a SEM image of a sodium ion positive electrode material of Comparative Example 2 of the present invention.

[0035] Fig.14This is an XRD diagram of a sodium ion positive electrode material of Comparative Example 2 of the present invention.

[0036] Fig.15 This is the 0.1C first charge and discharge curve of the sodium ion positive electrode material of Comparative Example 2 of the present invention.

[0037] Fig.16 This is a cycle performance diagram of the sodium ion positive electrode material of Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0038] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0039] Example 1

[0040] As a sodium ion positive electrode material in an embodiment of the present invention, the chemical formula of the sodium ion positive electrode material is Na x Ca y Ni a Fe b Mn c Ti d TM e O 2 , wherein TM is Mg, x=1.0, y=0.02, a=0.4, b=0.15, c=0.30, d=0.15, e=0.04, and the sodium ion positive electrode material is an O3 type sodium ion positive electrode material.

[0041] Ni a Fe b Mn c Ti d (OH) 2 The precursor, the sodium source, the calcium source, and the TM source are fully mixed in a high-efficiency mixer according to a stoichiometric ratio, and then calcined at 800° C. in an air atmosphere for 2 h, and then the temperature is further raised to 950° C. and calcined for 12 h, and then cooled naturally to obtain the sodium ion positive electrode material of this embodiment;

[0042] The sodium source is sodium carbonate, the calcium source is calcium carbonate, and the TM source is the oxide of the corresponding element.

[0043] Embodiments 2 to 6

[0044] As a sodium ion positive electrode material of an embodiment of the present invention, the only difference between this embodiment and embodiment 1 is that there is a difference in TM, and the total content of TM in the material remains unchanged.

[0045] Example TM TM element ratio Example 2 Mg、Sr 1:1 Example 3 Mg, Y 1:1 Example 4 Mg, Sr, Nb 1:1:1 Example 5 Mg、Al 1:1 Example 6 Mg, La 1:1

[0046] Example 7

[0047] As a sodium ion positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Embodiment 3 is that y=0.01.

[0048] Example 8

[0049] As a sodium ion positive electrode material of an embodiment of the present invention, the only difference between this embodiment and Embodiment 3 is that y=0.03.

[0050] Comparative Example 1

[0051] As a sodium ion positive electrode material of the comparative example of the present invention, the chemical formula of the sodium ion positive electrode material is Na x Ni a Fe b Mn c Ti d TM e O 2 , wherein TM is Mg and Y, the element ratio is 1:1, x=1.0, a=0.4, b=0.15, c=0.30, d=0.15, e=0.04, and the sodium ion positive electrode material is an O3 type sodium ion positive electrode material.

[0052] Comparative Example 2

[0053] As a sodium ion positive electrode material of the comparative example of the present invention, the chemical formula of the sodium ion positive electrode material is Na x Ca y Ni a Fe b Mn c Ti d TM e O 2 , wherein TM is Y and Al, the element ratio is 1:1, x=1.0, y=0.02, a=0.4, b=0.15, c=0.30, d=0.15, e=0.04, and the sodium ion positive electrode material is an O3 type sodium ion positive electrode material.

[0054] Comparative Example 3

[0055] As a sodium ion positive electrode material of the comparative example of the present invention, the chemical formula of the sodium ion positive electrode material is Na x Ca y Ni a Fe b Mn c Ti d TM e O 2, wherein TM is Y and Nb, the element ratio is 1:1, x=1.0, y=0.02, a=0.4, b=0.15, c=0.30, d=0.15, e=0.04, and the sodium ion positive electrode material is an O3 type sodium ion positive electrode material.

[0056] Comparative Example 4

[0057] As a sodium ion positive electrode material of the comparative example of the present invention, the chemical formula of the sodium ion positive electrode material is Na x Ca y Ni a Fe b Mn c Ti d TM e O 2 , wherein TM is Zr and Nb, the element ratio is 1:1, x=1.0, y=0.02, a=0.4, b=0.15, c=0.30, d=0.15, e=0.04, and the sodium ion positive electrode material is an O3 type sodium ion positive electrode material.

[0058] Experimental methods

[0059] 1. Material Characterization

[0060] 1. If Figure 1 This is a SEM image of the sodium ion positive electrode material of Example 1 of the present invention.

[0061] 2. If Figure 2 This is the XRD diagram of the sodium ion positive electrode material of Example 1 of the present invention.

[0062] 3. If Figure 5 This is a SEM image of the sodium ion positive electrode material of Example 3 of the present invention.

[0063] 4. If Figure 6 This is the XRD diagram of the sodium ion positive electrode material of Example 3 of the present invention.

[0064] 5. If Fig. 9 This is a SEM image of the sodium ion positive electrode material of Comparative Example 1 of the present invention.

[0065] 6. If Fig.10 This is the XRD diagram of the sodium ion positive electrode material of Comparative Example 1 of the present invention.

[0066] 7. If Fig.13 This is a SEM image of the sodium ion positive electrode material of Comparative Example 2 of the present invention.

[0067] 8. If Fig.14 This is the XRD diagram of the sodium ion positive electrode material of Comparative Example 2 of the present invention.

[0068] Depend on Figure 1, Figure 2 , Figure 5 , Figure 6 , Fig. 9 , Fig.10 , Fig.13 , Fig.14 It can be seen that the present invention uses sodium doping Ca 2+ The molar ratio of sodium and calcium is controlled at the same time, and Ti and Mg are used as necessary doping elements at the transition metal position, so that the O3 type sodium ion positive electrode material forms a more stable crystal structure.

[0069] 2. Battery performance testing method

[0070] Test method: The positive electrode materials obtained in Examples 1-8 and Comparative Examples 1-4 were used as active materials, and mixed according to the mass ratio of active material: conductive agent (Super P): binder (PVDF) of 90:5:5. An appropriate amount of solvent NMP was added to adjust the solid content. After being stirred into slurry by a pulping machine, it was coated on aluminum foil. After coating, the pole piece was dried in an oven at 110°C for 4 hours. Sodium sheet was used as the negative electrode, glass fiber as the diaphragm, and 1M NaPF6 (solvent EC:DEC=1:1Vol%) as the electrolyte, and button cells were assembled in a glove box. The battery was tested in the voltage range of 2.0 to 4.15V, activated at 0.1C for two weeks, tested the rate performance at 0.2C and 0.5C for one week each, and then the 1C50 cycle performance test was carried out.

[0071]

[0072]

[0073] Figure 3 This is the 0.1C first charge and discharge curve of the sodium ion positive electrode material of Example 1 of the present invention. Figure 4 This is a cycle performance diagram of the sodium ion positive electrode material of Example 1 of the present invention. Figure 7 This is the 0.1C first charge and discharge curve of the sodium ion positive electrode material of Example 3 of the present invention. Figure 8 This is a cycle performance diagram of the sodium ion positive electrode material of Example 3 of the present invention. Fig.11 This is the 0.1C first charge and discharge curve of the sodium ion positive electrode material of Comparative Example 1 of the present invention. Fig.12 This is a cycle performance diagram of the sodium ion positive electrode material of Comparative Example 1 of the present invention. Fig.15 This is the 0.1C first charge and discharge curve of the sodium ion positive electrode material of Comparative Example 2 of the present invention. Fig.16 This is a cycle performance diagram of the sodium ion positive electrode material of Comparative Example 2 of the present invention.

[0074] Depend on Figure 3 , 4, 7, 8, 11, 12, 15, 16 and Table 1 show that the sodium ion positive electrode material of the present invention is doped with Ca 2+ By controlling the molar ratio of sodium and calcium at the same time and using Ti and Mg as necessary doping elements at the transition metal position, the O3 type sodium ion positive electrode material can form a more stable crystal structure. After the working potential is increased to above 4.15V, the above O3 type sodium ion battery material takes into account both specific capacity and cycle stability and effectively increases the discharge median voltage.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A sodium ion positive electrode material, characterized in that: The chemical formula of the sodium ion positive electrode material is Na x Ca y Ni a Fe b Mn c Ti d TM e O2, wherein TM is at least one of Mg, Sr, Zr, Y, Al, La, Zn, Nb metal elements and must contain Mg, 0.5≤x≤1.1, 0.01≤y≤0.1, 0.1≤a≤0.5, 0.05≤b≤0.3, 0.1≤c≤0.4, 0.01≤d≤0.3, 0.01≤e≤0.1, and the sodium ion positive electrode material is an O3 type sodium ion positive electrode material.

2. The sodium ion positive electrode material according to claim 1, characterized in that: TM is at least two of the metal elements Mg, Sr, La, Y, Al, and Nb and necessarily contains Mg.

3. The sodium ion positive electrode material according to claim 2, characterized in that: TM is two or three of Mg, Sr, and Y and necessarily contains Mg.

4. The sodium ion positive electrode material according to claim 1, characterized in that: 0.8≤x≤1.1, 0.01≤y≤0.05, 0.25≤a≤0.50, 0.1≤b≤0.25, 0.2≤c≤0.35, 0.1≤d≤0.3, 0.02≤e≤0.

05.

5. The sodium ion positive electrode material according to claim 1, characterized in that: 0.95≤x≤1.05, 0.02≤y≤0.

03.

6. The sodium ion positive electrode material according to claim 1, characterized in that: The preparation method of the sodium ion positive electrode material comprises the following steps: Ni a Fe b Mn c The Tid(OH)2 precursor is fully mixed with the sodium source, calcium source and TM source in a stoichiometric ratio, calcined at 700-900°C in an air atmosphere for 1.5-2.5h, then heated to 900-1000°C for 10-14h, and then cooled naturally to obtain the sodium ion positive electrode material.

7. The method for preparing the sodium ion positive electrode material according to any one of claims 1 to 6, characterized in that: The method comprises the following steps: Ni a Fe b Mn c The Tid(OH)2 precursor is fully mixed with the sodium source, the calcium source and the TM source in a stoichiometric ratio, calcined at 700-900°C for 1.5-2.5h, then continued to heat to 900-1000°C for 10-14h, and then cooled naturally to obtain the sodium ion positive electrode material; The sodium source is sodium carbonate, the calcium source is calcium carbonate or calcium oxide, and the TM source is the oxide or hydroxide of the corresponding element.

8. A material composition for a positive electrode of a sodium ion battery, characterized in that: The invention comprises 80 to 100 parts by weight of the sodium ion positive electrode material as claimed in any one of claims 1 to 6, 4 to 6 parts by weight of conductive carbon black, and 4 to 6 parts by weight of polyvinylidene fluoride.

9. A positive electrode of a battery, characterized in that: The invention comprises 80 to 100 parts by weight of the sodium ion positive electrode material as claimed in any one of claims 1 to 6, 4 to 6 parts by weight of conductive carbon black, and 4 to 6 parts by weight of polyvinylidene fluoride.

Citation Information

Patent Citations

  • Sodium-ion battery positive electrode material and preparation method thereof

    CN116130644A

  • O3 type sodium ion positive electrode material, preparation method thereof and sodium ion battery

    CN116495799A

  • O3 type sodium ion positive electrode material and preparation method and application thereof

    CN117276521A

  • Cu, Mg and Ti co-doped O3 phase layered oxide sodium ion battery positive electrode material, preparation method and battery

    CN117996069A

  • Doping strategy for layered oxide electrode materials used in sodium-ion batteries

    US20230352672A1

Cited By

  • High-rate long-cycle sodium ion positive electrode material and preparation method thereof

    CN119833609A

  • A high-magnification long-cycle sodium-ion positive electrode material and a preparation method thereof

    CN119833609B

  • Sodium ion layered positive electrode material with composite structure and preparation method and application of sodium ion layered positive electrode material

    CN121237798A